THE SILENT RETURN OF THE SOUTH TO THE SOUTH: VERDONE’S PASQUALE AMETRANO AS A COUNTER-CHAPLIN - Messina, Marcello; Capogreco, Stefania (TROPOS: COMUNICAÇÃO, SOCIEDADE E CULTURA (ISSN: 2358-212X), 2019)
Carlo Verdone’s 1981 film Bianco, Rosso e Verdone is counted among Italy’s most loved comedy classics. The film contains the story of Pasquale Ametrano, a Southern Italian immigrant based in Munich who travels across Italy in order to vote in his hometown Matera. In this article we interrogate the figure of Pasquale in order to unveil the ways in which the film captures fundamental aspects of the experiences, identities and representations of diasporic subjects returning to Italy. In particular, we argue that Pasquale’s journey from the North to the South of Italy is a metaphor of the ruthless plunder that characterises the violent annexation of the South during the Unification period. Furthermore, we discuss the obstinate silence of the character, reading it both as a metaphor for his imposed voicelessness and as a political act that utters indignation against those who marginalise him. Finally, we compare Pasquale’s final rant with the last speech of Chaplin’s tramp in The Great Dictator.